2018
DOI: 10.1021/jacs.7b13526
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Hydricities of Biomimetic Organic Hydride Donors

Abstract: Thermodynamic hydricities (Δ G) in acetonitrile and dimethyl sulfoxide have been calculated and experimentally measured for several metal-free hydride donors: NADH analogs (BNAH, CN-BNAH, Me-MNAH, HEH), methylene tetrahydromethanopterin analogs (BIMH, CAFH), acridine derivatives (Ph-AcrH, MeN-AcrH, T-AcrH, 4OH, 2OH, 3NH), and a triarylmethane derivative (6OH). The calculated hydricity values, obtained using density functional theory, showed a reasonably good match (within 3 kcal/mol) with the experimental valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 134 publications
3
110
0
Order By: Relevance
“…26 We also demonstrated that the benzoimidazole-based hydrides can be efficiently regenerated electrochemically by optimizing the conditions for proton-coupled electron transfer, reporting the first proof-of-principle demonstration toward metal-free and selective CO2 reduction catalysis. 24,27 Despite the successful demonstration of HT to CO2, the kinetics of the transformation were quite slow in our studies, on the timescale of several hours.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…26 We also demonstrated that the benzoimidazole-based hydrides can be efficiently regenerated electrochemically by optimizing the conditions for proton-coupled electron transfer, reporting the first proof-of-principle demonstration toward metal-free and selective CO2 reduction catalysis. 24,27 Despite the successful demonstration of HT to CO2, the kinetics of the transformation were quite slow in our studies, on the timescale of several hours.…”
mentioning
confidence: 75%
“…22 Following in nature's footsteps, our group recently developed hydrides that mimic NADPH activity, and that are sufficiently hydridic to perform a direct reduction of CO2. [23][24][25][26][27][28] Our work has shown how the thermodynamic hydricities of metal-free hydrides can be tuned using aromatization, delocalization and hyperconjugation mechanisms and that the benzoimidazole-based hydride C4H ( Figure 1) can efficiently reduce CO2 to formate via the HT mechanism. 26 We also demonstrated that the benzoimidazole-based hydrides can be efficiently regenerated electrochemically by optimizing the conditions for proton-coupled electron transfer, reporting the first proof-of-principle demonstration toward metal-free and selective CO2 reduction catalysis.…”
mentioning
confidence: 95%
“…We also expect that this strategy will be useful for tuning of redox potentials important for photocatalysis, organic hydride donors and electrogenerated chemiluminescence applications where these cationic dye systems recently have shown promising results. [8][9][26][27] Finally, the chlorinated systems are obvious starting points for coupling reactions aiming for -system extension. [28][29][30] Experimental section: Synthetic Methods and Materials.…”
Section: Discussionmentioning
confidence: 99%
“…Our group is interested in metal‐free motifs capable of catalyzing electrochemical oxidation and reduction reactions . In our studies of the oxygen evolution reaction (OER), catalytic behavior was observed in an electrode‐assisted mechanism, where selected electrodes, such as glassy carbon and platinum, exhibited improved oxygen evolution performance in the presence of iminium or oxonium cations .…”
Section: Introductionmentioning
confidence: 99%
“…[10] Our group is interested in metal-free motifs capable of catalyzing electrochemical oxidation and reduction reactions. [11][12][13][14][15][16] In our studies of the oxygen evolution reaction (OER), catalytic behavior was observed in an electrodeassisted mechanism, where selected electrodes, such as glassy carbon and platinum, exhibited improved oxygen evolution performance in the presence of iminium or oxonium cations. [14][15][16] These results lead us to hypothesize that a fully homogeneous catalyst, composed of covalently linked organic cations (R + , such as iminium and oxonium ions), can catalyze the water oxidation process via alcohol (R-OH) and peroxide (R-O-O-R) intermediates, by the following sequence: (a) 2R…”
Section: Introductionmentioning
confidence: 99%